Policy Changes in Status of Forest Ownership from 1865 to 2006 - Journey from Government Owned to Private Ownership - an Analysis - Upadhyay, R. K. (Indian Forester, 2011)
The Government Forest Act, 1865 was the first Central Law with wider applicability enacted in India during British rule and was applicable to Bengal, Assam, North-Western Provinces, Oudh and Punjab, Central Provinces and Bombay. Its preamble was "for better management and preservation offorests" and rights were vested in Her Majesty for the purpose of Government of India. Under this Act, forests were defined in Section (1) as "Government Forests" shall mean such land covered with trees, brushwood or jungle and the ownership of such land shall vest with Government. Since then the status of ownership has not undergQne any major change with reference to status of ownership from 1894 Forest Policy (oldest Forest Policy) to 1988 National Forest Policy (current Forest Policy in force) as the bulk of ownership of forest land remain with Government. But now Forest Policy in India has undergone major changes leading to increased involvement of forest dependent communities in sustainably managing the forest resources on which they depend. Parliament have enacted legislation namely the Scheduled Tribes and Other Traditional Forest Dwellers (Recognition of Forest Right) Act, 2006, which recognizes the ownership right on forest land upto 4 ha perfamily. Nowthe important debate is whether India should adopt "Doctrine of Public Trust" theory and manage forest resource by keeping it under Trusteeship under State Control (Government control) or manage it with community under limited contractual agreement (without giving ownership to community e.g. Quasi contract) like joint forest management or shall it recognize ownership right to individual/community. Whether implementation of Scheduled Tribes and Other Traditional Forest Dweller Act (Recognition of Forest Right) Act 2006 (in short Forest Right Act 2006) is againstthe principle of Doctrine of Public Trust Theory?